Epidemiological Study of Trichomonas Vaginalis in Married females - Kadhum, Suha A. (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of this study was to identify the main risk factors with Trichomonas vaginalis infection in married women that have vaginal discharge. The study include (250) female who attended Al-Yarmouk Teaching Hospital (Gynecological Clinics), through the period from February 2010 to July 2010.Patients female were subjected for a special questionnaire sheet. The study has found that (65) females were infected with this parasite from total (250), who were complaining from vaginal discharge with infection rate 26%.Higher infection rate was recorded between pregnant female was 17.2% while non-pregnant women 8.8% .The main age group of infected women concentrated in (20-29 years) in which rate were 12.83% and 11.76% in pregnant and non-pregnant women respectively.According to educational level and socio-economic status, the study recorded higher percentage 50.76% between illiterate women and with low socio-economic status 63.07%.The highest infection with Trichomonas vaginalis obtained from women with white to gray discharge 58.46% and with bad odor 81.53%.Depending on residency, in rural residence the high percentage of infection were recorded 63.07% while comparing with urban 36.93%.Considering to contraceptive types which used by women 47.69% for IUDs, followed by 32.31% for contraceptive pills and low percentage for condom 20%.